Analysis of Product Defects in the Installation of Part Stage Housing Left Using the Seven Tools Approach at Pt. Electronic - Kurnia, Syafika Nugrah; Suwarno, Agus; Supriyati, Supriyati (Indonesian Journal of Advanced Research, 2024)
The fierce competition between industries today makes PT. Electronics must always be competitive. Product quality is the main factor in competing. Problems that arise at PT. Electronics is the quality of the cahill model printer product in the left housing stage that still has part defects. This study was conducted to determine the most dominant factors causing defects, identify the factors that cause part defects, determine the relationship between variable part defects and production results and also, to provide improvement proposals to PT. Electronics to reduce defective parts on the left stage housing. This study uses the 7 Tools method to find the root cause of the problem that is solved, Based on the results of the analysis of the data that has been collected, the results are obtained that the 6 types of defects obtained on the check sheet are defects, short mold, dirty, loose, scratch, bending, broken. Of the six types of defects, The highest percentage is the Scracth defect of 30.12%, Based on the fishbone diagram, it can be known that the defect is caused by several factors, namely from humans, materials, methods, and the environment. The relationship between the variable defect of the part and the production result is stated to be quite normal and can still be controlled if there is improvement. And the proposed problem improvement obtained is to conduct training to hone employee skills, check materials and work areas repeatedly, and widen the workspace.